HASIL BELAJAR KOGNITIF SISWA MELALUI PENERAPAN STRATEGI WHOLE BRAIN TEACHING DALAM PEMBELAJARAN IPA FISIKA DI KELAS VII SMPN 29 PEKANBARU - Nuri Wulandari; Azizahwati Azizahwati; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed to describe cognitive science in physics learning outcomes of students using whole brain teaching strategy on the issue states of matter and the changes. This study was conducted in SMP 29 Pekanbaru for October-December 2015. The subjects of this research were students of class VII2 as control class with conventional learning numbered 42 students and VII6 as a class experiment with whole brain teaching a total of 42 students. This study is pre-experimental design with static design of two groups. Instrument collecting data in this study is a cognitive performance test consists of 20 multiple choice items. The data collection techniques, by the administration of the test after learning. Data were analyzed with descriptive analysis that describe the absorption and effectiveness of learning. The results showed that to improve the absorption of the students after the implementation of whole brains learning strategies are 77,14% students categorized good. So that it is effective to improve the students cognive level and can be useed in science learning especially physich subject.Key Words: The cognitive learning, Joyful Learning, Descriptive Analysis, Learning absorption and effectivity